MEMBEDAH STEREOTIP GENDER: PERSEPSI KARYAWAN TERHADAP SEORANG GENERAL MANAGER PEREMPUAN - Sany, Nukhbah; Rahardja, Edy (Diponegoro Journal of Management, 2016)
Women who decided to work has several reasons, i.e. for self-actualization and help fulfilling the financial needs of the family. However, the number of women who became a manager (non-entrepreneurs) is still small when compared with the number of male leaders. Women who have positions as a leader of a company have more responsibility and perceived as different compared to the regular career woman. The study was conducted to understand how the perception of the employees against their female manager from the standpoint of gender stereotypes.            This study uses a qualitative research as research methods and phenomology as research approach. Samples taken in this study were 8 persons, of whom 1 female General Manager, 1 male manager, and 6 employees of women and men. The interviewees are derived from the same division, in order to maximize the data obtained.            The results of this study include: (1) Female General Manager doesn’t experience discrimination in the work environment caused by gender, (2) leadership effectiveness by the female General Manager rated good by the employees, (3) the leadership style associated with the communal traits adopted General Manager of women (transformational leadership) preferred by employees, and (4) family and communal negative traits possessed by General Manager caused inhabitation for her career development and self development. The study also provides results that (4) the traits related to gender do not affect the outcome of the evaluation and promotion given by the leaders.